Think-Pair-Square: A Collaborative Approach to Enhancing Critical Thinking Skills in Chemical Equilibrium - Hilga Natasya Sinaga; Yuli Hartati; Farah Erika (Journal of Educational Chemistry (JEC), 2025)
Low levels of critical thinking skills among students on the topic of chemical equilibrium pose a significant challenge in chemistry education. This topic demands strong analytical, evaluative, and problem-solving abilities. This study aimed to investigate the effectiveness of the Think-Pair-Square (TPSq) learning model in enhancing students’ critical thinking skills. A pre-experimental one-group pretest–posttest design was employed, involving 59 students from two classes selected through cluster random sampling. Data were collected using a critical thinking skills test administered before and after the intervention, and analyzed using N-Gain and effect size. The results indicated a significant improvement in students’ critical thinking skills, with an average N-Gain of 0.48 (moderate category) and an effect size of 2.75 (very high category). These findings suggest that TPSq is an effective collaborative learning strategy for developing critical thinking skills in chemical equilibrium and can serve as an alternative instructional method that promotes student interaction and discussion.